2019
DOI: 10.1093/rheumatology/kez576
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cardiovascular risk in users versus non-users of xanthine oxidase inhibitors and febuxostat versus allopurinol users

Abstract: Objectives The aim of this study is to determine major adverse cardiovascular events (MACE) and all-cause mortality comparing between xanthine oxidase inhibitors (XOIs) and non-XOI users, and between allopurinol and febuxostat. Methods This is a retrospective cohort study of gout patients prescribed anti-hyperuricemic medications between 2013 and 2017 using a territory-wide administrative database. XOI users were matched 1:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 43 publications
(56 reference statements)
0
53
1
1
Order By: Relevance
“…This has previously been used by local teams for conducting research studies. [15][16][17] The following clinical details were obtained: age, gender, smoking status, diabetes mellitus, hypercholesterolaemia, coronary artery disease, hypertension, baseline atrial fibrillation (AF), and anti-hypertensive and anti-coagulation medications. Complete blood count was performed using automated haematology analysers.…”
Section: Study Population Baseline Characteristics and Laboratory Imentioning
confidence: 99%
“…This has previously been used by local teams for conducting research studies. [15][16][17] The following clinical details were obtained: age, gender, smoking status, diabetes mellitus, hypercholesterolaemia, coronary artery disease, hypertension, baseline atrial fibrillation (AF), and anti-hypertensive and anti-coagulation medications. Complete blood count was performed using automated haematology analysers.…”
Section: Study Population Baseline Characteristics and Laboratory Imentioning
confidence: 99%
“…Some of the subsequent studies however have shown variable outcomes. A recent observational study comparing febuxostat and allopurinol with controls showed a similar incidence of major adverse CV events in both groups, while patients receiving febuxostat had a lower incidence of HF hospitalization [50]. Further information from the LEAF-CHF (Effect of urate LowEring Agent Febuxostat in Chronic Heart Failure patients with hyperuricemia) trial, in which patients with HF (left ventricular ejection fraction < 40%) and hyperuricemia (7.0-10.0 mg/day) are randomized to febuxostat or placebo, with a primary endpoint of difference in plasma B-type natriuretic peptide (BNP) from baseline to 24 weeks, may help elucidate the effect of febuxostat in HF [51].…”
Section: Febuxostatmentioning
confidence: 94%
“…This is a retrospective cohort study nested within the territory-wide Clinical Data Analysis and Reporting System (CDARS), an electronic health record system managed by the Hong Kong Hospital Authority since 1995. The database included over 7 million Hong Kong residents and has been used for producing high-quality clinical studies (26, 27). Patient information was de-identified with pseudo-identity numbers.…”
Section: Methodsmentioning
confidence: 99%